ErbB4 precludes the occurrence of PTSD-like fear responses by supporting the bimodal activity of the central amygdala - Kibong Sung; Min-Jae Jeong; Taesik Yoo; Jung Hoon Jung; Sumin Kang; Jong-Yeon Yoo; Hyun Jin Kim; Kyunghyun Park; Jung Hyun Pyo; Hyun-Yong Lee; Noah Koo; Soo-Hee Choi; et al. (Experimental and Molecular Medicine)
Abstract Post-traumatic stress disorder (PTSD) often arises after exposure to traumatic events and is characterized by dysregulated fear responses. Although the associations of erb-b2 receptor tyrosine kinase 4 (ErbB4) with various neuropsychiatric diseases, including schizophrenia and bipolar disorder, have been widely examined, the physiological roles of ErbB4 in PTSD and fear responses remain unclear. Using Cre-dependent ErbB4 knockout (KO) mice, we observed that PTSD-like fear behaviors emerged in ErbB4-deficient mice, particularly in inhibitory neurons. Specifically, the loss of ErbB4 in somatostatin-expressing (SST+) neurons was sufficient to induce PTSD-like fear responses. We also adopted the CRISPR/Cas9 system for region-specific KO of ErbB4, which revealed that ErbB4 deletion in SST+ neurons of the lateral division of the amygdala (CeL) caused elevated anxiety and PTSD-like fear generalization. Consistent with its physiological role, ErbB4 expression was diminished in CeLSST neurons from mice that exhibited PTSD-like phenotypes. While fear On and Off cells identified in the CeL displayed distinct responses to conditioned and novel cues, as previously shown, the selectivity of those On and Off cells was compromised in SSTErbB4-/- and stressed mice, which displayed strong fear generalization. Therefore, the bimodal activity that CeL On/Off cells display is likely required for proper discrimination of fearful stimuli from ambient stimuli, which should be sustained by the presence of ErbB4. Taken together, our data substantiate the correlation between PTSD-like fear responses and ErbB4 expression in CeLSST neurons and further underscore the functional effects of ErbB4 in CeLSST neurons, supporting the bimodal responses of CeL neurons.